Assessing the potential of demand-side flexibility to improve the performance of electricity systems under high variable renewable energy penetration. (1st June 2023) - Saffari, Mohammadali; Crownshaw, Timothy; McPherson, Madeleine
Abstract: Increasing the deployment of variable renewable energy (VRE) resources is a prominent option for the decarbonization of Canada's electricity system. One of the most important challenges with rising VRE penetration is providing sufficient network flexibility. This study analyzes the potential impact of demand-side flexibility, via two distinct demand response formulations, to network flexibility under VRE-dominated scenarios in Alberta, Canada. A coupled framework consisting of an electricity system operation model (SILVER) and a capacity expansion model (COPPER), both developed for the Canadian context, is used here for this purpose. In this framework, capacity expansion scenarios are identified using COPPER, based on Canada's decarbonization targets for 2050, followed by modeling using SILVER to investigate the effect of demand response programs on operational costs and VRE curtailment. Results indicate that demand response programs can decrease VRE curtailment by approximately 44–64% by 2050 in Alberta, alongside reductions in direct operational costs of $4–8 million per month. Notably, these results are considered robust due to the high spatial and temporal resolutions made possible by the coupled modeling framework. Highlights: The impacts of demand-side flexibility on a VRE-dominated network are assessed using a novel coupled modeling framework. Modeled network flexibility and associated impacts are sensitive to the parameterization of demand response programs. The effectiveness of demand response programs is limited by transmission network capacity. Demand response program implementation likely worsens network congestion, raising important economic trade-offs. The direct real-world benefits of demand-side flexibility may be less than commonly indicated in the literature.